Diffuse Gastric Ganglioneuromatosis: Novel Presentation of PTEN Hamartoma Syndrome—Case Report and Review of Gastric Ganglioneuromatous Proliferations and a Novel PTEN Gene Mutation - Alexander J. Williams; Emily S. Doherty; Michael H. Hart; Douglas J. Grider (Case Reports in Medicine)
Gastrointestinal ganglioneuromatous proliferations are rare, most often found in the colon, and are three types: polypoid ganglioneuromas, ganglioneuromatous polyposis, and diffuse ganglioneuromatosis. We present a case of diffuse ganglioneuromatosis in the posterior gastric wall in a nine-year-old female. To our knowledge, this is the first reported case of diffuse ganglioneuromatosis located in the stomach. Only six cases of gastric ganglioneuromatous proliferations have previously been reported, two in English and none were diffuse ganglioneuromatosis. A diagnosis of diffuse ganglioneuromatosis is relevant for patient care because, unlike sporadic polypoid ganglioneuromas or ganglioneuromatous polyposis, most are syndromic. Diffuse ganglioneuromatosis is commonly associated with neurofibromatosis type 1, multiple endocrine neoplasia type 2b, and Cowden Syndrome, one of the phenotypes of PTEN hamartoma tumor syndrome. The patient had the noted gastric diffuse ganglioneuromatosis, as well as other major and minor criteria for Cowden syndrome. Genetic testing revealed a novel frameshift mutation in the PTEN gene in the patient, her father, paternal aunt, and the aunt’s son who is a paternal first cousin of the patient.